If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 82 + -5x Reorder the terms: 12 + 3x = 82 + -5x Solving 12 + 3x = 82 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 12 + 3x + 5x = 82 + -5x + 5x Combine like terms: 3x + 5x = 8x 12 + 8x = 82 + -5x + 5x Combine like terms: -5x + 5x = 0 12 + 8x = 82 + 0 12 + 8x = 82 Add '-12' to each side of the equation. 12 + -12 + 8x = 82 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = 82 + -12 8x = 82 + -12 Combine like terms: 82 + -12 = 70 8x = 70 Divide each side by '8'. x = 8.75 Simplifying x = 8.75
| 10*x-12+5*x-2*x=2*x+8-5 | | 2t-9=3-t | | 3r^2-16r+14=0 | | 3x+75=123 | | -2.5p=5(10-0.5)p | | (9x-5)(8x+9)=0 | | -3w=-12 | | 4c-31=53 | | logxy^3= | | 0.26n=2.34 | | 3.5x-12-7x=58 | | X^2-2x+83=0 | | -48+(-10)= | | (x-6)(x-6)(3)=108 | | (x-6)(x-6)=108 | | 7(2y-3)-(5y+7)= | | 8x^3-5x^2=72x-45 | | 1.31x=5.24 | | 7x+22=y | | 9y^3=-9y^2+10y | | 5x-2(x-4)=10(x-2) | | 8+5(4+4)-6= | | 7x-5=7x+3 | | 3(a+1)=7(a-9) | | 10x+15y=5 | | 5x+8y=49 | | 10x+15y=5(x+y) | | x^2-99x-2=0 | | e^7x+1=14 | | 8y^2-3y+5y^2-4y= | | (6-2)4+2(8-5)= | | 3p^2-5p-28=0 |